Enhancing the thermoelectric power factor of nanostructured SnO2 via Bi substitution. Issue 7 (1st April 2023) - Ashfaq, Arslan; Smirani, Lassaad K.; Abboud, Mohamed; Rehman, Ubaid ur; Fadhali, Mohammed M.; Hegazy, H.H.; Hossain, Md Amzad; Ali, A.; Mehmood, K.; Amin, N.
Abstract: Tin dioxide (SnO2 ) has recently proved to be a promising material for thermoelectric applications. We have investigated the influence of highly valence Bi doping as an electron donor in oxygenated SnO2 materials on their thermoelectric properties. We have synthesized the pure and Bi doped SnO2 nanoparticles (x = 0%, 5%, 10%, and 15%) through a simple hydrothermal approach. The Seebeck coefficient and Hall measurements have been used to determine thermoelectric behaviour. The measured value of the Seebeck coefficient increases from - 56 to - 83 μV/ ° C as the Bi content increases. This improvement in the Seebeck coefficient has been attributed to the charge carrier localization (energy filtering effect) caused by the inclusion of the bismuth atoms and the presence of secondary phases based on BiO2 . However, the electrical conductivity measurements show an inverse relation with the Bi doping, increasing the impurities. The Sn1-x Bix O2 sample with x = 15 has achieved the maximum Seebeck value, resulting in the upward trend in power factor of up to 1.97 × 10 −4 Wm −1 C −2 . Further, we have used X-ray diffraction and scanning electron microscopy to determine the effect of Bi on the SnO2 crystal structure and surface morphology. Which also demonstrates the presence of composites with mixed phases.